Reproduction of the south american endemic shrimp artemesia longinaris in a marine protected area - Bernardo, Camila Hipolito [UNESP]; Sancinetti, Gustavo Sérgio; de Sousa, Aline Nonato [UNESP]; da Silva, Thiago Elias [UNESP]; da Costa, Rogério Caetano [UNESP]; Fransozo, Adilson (Taylor & Francis, 2018)
Artemesia longinaris was analyzed here with respect to reproductive period, recruitment and sexual maturity. Samples were carried out in five transects, monthly, from November 2008 to October 2009, at Fortaleza Bay, north coast of the State of São Paulo, in Brazil, in a region recently decreed as a Marine Protected Area. In total, 1173 individuals were captured: 198 juveniles, 97 rudimentary females, 485 breeding females and 409 adult males. Breeding females and juveniles appeared seasonally and their abundances were positively corelated with bottom water salinity and temperature. The female size at the onset of sexual maturity was estimated as 13.29 mm of carapace length. Our results indicated that Fortaleza Bay can be considered an appropriate place for the reproduction of A. longinaris during summer, because the environmental conditions there in this period are favourable. We suggest that the fishing ban period should be adequate to take into account the reproductive behaviour of other shrimp species, such as A. longinaris, since it is currently based only on the recruitment of species of Farfantepenaeus.
Keywords: Artisanal fishing; Penaeidae; Sexual maturity; Southern Atlantic Central Water; ‘barba-ruça’